THE PREVALENCE OF ALLERGIC CONJUNCTIVITIS AMONG CHILDREN, DEPENDING ON THE PLACE OF RESIDENCE - Abdiyeva, Ya.J. (World of Medicine and Biology, 2021)
The study was carried out in the Ganja-Gazakh economic region of Azerbaijan. The total of 2,700 children and adolescents were observed: 300 children (150 boys and 150 girls) in each age group (5–9; 10–14; 15–19) in each type of locality (large city, small towns and rural settlements). The prevalence of allergic conjunctivitis at the age of 5–9 years and adolescents aged 10–14 years (19.4±1.3 % and 17.7±1.3 %) does not significantly differ from each other, but at the age of 15–19 years, this index increases statistically and is 25.8±1.5 %. In the family history of patients with allergic conjunctivitis, this pathology occurs in 42.1±2.1 % of cases in brothers and sisters, in 28.1±1.9 % of cases in mothers, in 22.6±1.8 % of cases in fathers, in 20.9±1.7 % of cases in other relatives. Patients with allergic conjunctivitis have a high relative risk of developing bronchial asthma (by 16.4 times), rhinitis, sinusitis and rhinosinusitis (by 2.4 times), otitis (by 1.8 times) and tonsillitis (by 2.0 times).